Factors influencing human development in regencies/cities of Lampung Province (2017–2021): An Islamic economics perspective - Salma, Novi Qistina; Devi, Yulistia; Nurhayati, Nurhayati (Nur Science Institute, 2024)
The regency/city Human Development Index in Lampung Province grew slowly in 2017-2021. Lampung Province ranks lowest of the ten provinces on the island of Sumatra in 2021, even though government spending in the education sector and per capita income continue to increase while the percentage of poor people has decreased relatively. This research aims to determine the effect of government spending on the education sector, per capita income and poverty on the HDI of regencies/cities in Lampung Province and to explain HDI from an Islamic economic perspective. The data sources were obtained from the Central Agency of Statistics and the Directorate General of Fiscal Balance in 2017-2021. Panel data regression was used to analyze the data in this study. The results showed that partial government expenditure in the education sector and poverty had a significant effect on the HDI of regencies/cities in Lampung Province, while per capita income had no significant effect on the HDI of regencies/cities in Lampung Province.